If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 182 + -1u = 47 Solving 182 + -1u = 47 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-182' to each side of the equation. 182 + -182 + -1u = 47 + -182 Combine like terms: 182 + -182 = 0 0 + -1u = 47 + -182 -1u = 47 + -182 Combine like terms: 47 + -182 = -135 -1u = -135 Divide each side by '-1'. u = 135 Simplifying u = 135
| 3=x/6-5 | | 3x^4-16x^2+16=0 | | cos65=15/x | | 3(x-1)=-18 | | -18y^4/-6y^2 | | 8(3x+4)=18(x+5) | | 12.8=x/4 | | 50/60=10/x | | (2x-1)(4x+4)=0 | | 2/7w=42 | | 7v=14/5 | | 10t+4=-36 | | X(4/9x)=576 | | 8/2=13-3 | | 3log(x^2)+2log(4x)=3 | | log[2](3x-4)=5 | | 3x+6+x=16 | | 5×1/3= | | 75=2x+1(x) | | 5×1/3 | | 12.4y+24=6y-2 | | 3x-10=-x^2 | | x^2-kx+3-k=0 | | 75=2x+1-x | | 5x1/3= | | 4.3p=5 | | 3x+8=15w+4 | | -2x/5-8-7 | | 3x+6+x=4 | | 1/4(10x-2)=7 | | 17g+3=g+39 | | 5-24/5 |